Symbiodiniaceae and Bacterial Microbiome Dynamics Differentially Impact the Survival of Dominant Reef‐Flat Porites Corals - Colin Lock; Therese C. Miller; Colin J. Anthony; Héloïse Rouzé; James Fifer; Grace McDermott; Carlos A. Tramonte; Loreto Paulino; Sarah W. Davies; Laurie Raymundo; Bastian Bentlage (Environmental Microbiology, 2025)
Coral reefs face significant threats across the globe, prompting a surge in restoration efforts aimed at mitigating their global decline. The health, resilience, and adaptability of corals are greatly influenced by their microbial communities, and while the response of coral microbiomes to many environmental stressors has been extensively studied, less is known about their natural dynamics following transplantation, which is an essential process for restoring degraded reef habitats. In this study, we integrated DNA metabarcoding (16S & ITS2) with ecological monitoring to investigate the dynamics of Symbiodiniaceae and bacterial communities in two dominant coral spp., Porites lobata and Porites cylindrica , and their different colour morphs, as they underwent transplantation and an 18‐week acclimatisation period. We saw significant differences in microbial communities between the two Porites spp., outplanting sites, and individual coral colonies, as well as a colour morph‐related difference in P. lobata bacterial communities. We saw reduced relative abundances of Endozoicomonadaceae, specifically from the genus Parendozoicomonas, following transplantation. P. lobata colonies with later Symbiodiniaceae shifts (18 weeks) had lower long‐term survival. Changes in Symbiodiniaceae and bacterial communities have implications for holobiont function and colony survival, which should be considered when designing and implementing coral reef rehabilitation projects.

Symbiodiniaceae phenotypic traits as bioindicators of acclimatization after coral transplantation - Colin J. Anthony; Colin Lock; Gonzalo Pérez-Rosales; Héloïse Rouzé; Loreto Paulino; Laurie J. Raymundo; Bastian Bentlage (Marine Pollution Bulletin, 2024)

Depth‐independent phenotypic variation of massive Porites coral color morphs - Colin J. Anthony; Grace McDermott; Colin Lock; Therese Miller; Bastian Bentlage; Laurie J. Raymundo (Marine Ecology, 2024)
As coral reefs continue to decline due to anthropogenic stressors, community characterizations will reveal both historical selection processes and adaptive potential to environmental change. To address the potential role of color in the distribution and resilience of massive Porites corals, we surveyed the distributions of two dominant color morphs (brown and purple), and a unique intermediate state, across a depth gradient in Guam, Micronesia. We found that brown colonies dominated populations across all depths, and larger colonies had higher rates of partial tissue mortality and active disease lesions. Despite the dominance of brown colonies, both brown and purple color morphs showed a high similarity in susceptibility, as indicated by the colony sizes, the severity of partial tissue mortality, and the prevalence of active disease lesions. This is a non‐intuitive result given the presence of phenotypic plasticity between color morphs, evident by an intermediate, transitionary stage between brown and purple colonies that suggests a functional divergence between one color over the other. The study also revealed the dominance of small colonies at depth, which provides some insight into the ecological impacts that may have shaped Guam's current massive Porites population size structure over the past several decades. With this, we provide foundational insight into the adaptive strategies and historical pressures that have shaped the modern massive Porites population.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

A comparison of the short-term toxicity of cadmium to indigenous and alien gammarid species - Pieter Boets; Koen Lock; Peter L. M. Goethals; Colin R. Janssen; Karel A. C. De Schamphelaere (Ecotoxicology, 2012)

Cadmium Toxicity for Terrestrial Invertebrates: Taking Soil Parameters Affecting Bioavailability Into Account - Koen Lock; Colin R. Janssen (Ecotoxicology, 2001)

Test Designs to Assess the Influence of Soil Characteristics on the Toxicity of Copper and Lead to the Oligochaete Enchytraeus albidus - Koen Lock; Colin R. Janssen (Ecotoxicology, 2001)